Xunzi on the origin of goodness : a new interpretation - Li, Chenyang (2012)
This essay explores a seeming mystery in the philosophy of Xunzi (荀子310-238 BCE), namely how goodness could have emerged in a world of people with only a bad human nature. I will examine existing interpretations and present a new reading of Xunzi. My purpose is to reconstruct a coherent view in Xunzi‟s philosophy as presented in the book of the Xunzi rather than defend the truth of his claims regarding human history.